2013
DOI: 10.2190/pm.45.1.a
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Postpartum Adaptation and Postpartum Depression Symptoms of First Pregnancy Mothers in Taiwan

Abstract: This study shows that healthcare providers who work with primiparas during the first 2 months after giving birth should pay more attention to postpartum depression, keeping in mind associated risk factors. A new mother's confidence in her own abilities as a new mother may be particularly important in determining the likelihood of postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The prevalence of patients with PPD screened by the EPDS in Taiwan was found to be 21%, 42%, and 39% in 2004, 2007, and 2013, respectively [13,14,15]. The incidence of PPDS in this study was thus significantly lower than in these past surveys.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The prevalence of patients with PPD screened by the EPDS in Taiwan was found to be 21%, 42%, and 39% in 2004, 2007, and 2013, respectively [13,14,15]. The incidence of PPDS in this study was thus significantly lower than in these past surveys.…”
Section: Discussioncontrasting
confidence: 53%
“…The Chinese version of the EPDS has appropriate reliability and validity for screening for PPD among Taiwanese women [12]. The prevalence of PPD screened using the EPDS in Taiwan was 21%, 42%, and 39% in 2004, 2007, and 2013, respectively [13,14,15]. The results of these studies also indicated that cesarean section, postpartum complications, a previous history of depression, unplanned pregnancy, low income, and a lack of familial support increase PPDS risk.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 13 studies addressing family support (including mother, mother-in-law, and general family), 10 found significant negative associations (#51, 77, 104, 105, 108, 117, 134, 161, 171, 176) and 3 found no effect on PPD risk despite relatively large samples (#75, 123, 142). Three studies combining low perceived support from family and friends also found significant univariate associations with elevated PPD symptoms and risk (Ho et al 2013, Ramchandani et al 2009, Rich-Edwards et al 2006). However, social support from other women with children or from friends was not associated with PPD symptoms after controlling for other risk factors (Dennis et al 2004, Secco et al 2007, Siu et al 2012).…”
Section: Psychosocial Predictors Of Postpartum Depressionmentioning
confidence: 93%
“…Mother's non-employment was found to be significantly correlated with PPD (r=0.201, sig=0.45). Aligned with previous finding, mothers who experience PPD are mostly non-working mothers or housewives and mothers with part-time type of employment compared to full-time working mothers (Bener, Burgut, Ghuloum, & Sheikh, 2012;Ho, Chang, & Wan, 2013). It is because in postpartum period, financial issue is a factor that affects the onset of PPD (Bener et al, 2012).…”
Section: Discussionmentioning
confidence: 58%